Efektivitas Pajak Hiburan di Kabupaten Garut - Mukhsin Abdul Gopur; Marti Dewi Ungkari; Lina Nurlaela (Jurnal Wahana Akuntansi, 2024)
This study aims to determine the level of effectiveness of entertainment tax collection in Garut Regency. This research was conducted at the Regional Revenue Agency of Garut Regency. The research method used is a qualitative method with a descriptive approach, the source of the data needed in this study is primary data. This data was obtained directly from the Bapenda Garut Regency. Data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The results of the study indicate that the effectiveness of the entertainment tax in Garut Regency as a whole when referring to the criteria that have been set based on Kepmendagri No. 690.900.327 in 1996, it can be concluded that the effectiveness of entertainment tax revenue in Garut Regency from 2016-2020 in the criteria is very effective with an average effectiveness level of 106.25%. This shows that the government of Garut Regency has been able to carry out entertainment tax collection very effectively. Where the entertainment tax collection system uses a self-assessment system, while the entertainment tax collection procedure in Garut Regency starts from reporting, payment to billing.